PENGARUH PROMOSI PENJUALAN TERHADAP KEPUTUSAN KONSUMEN PENGGUNA JASA KREDIT SEPEDA MOTOR MEREK HONDA PADA PT. CAPELA MULTIDANA CABANG PEKANBARU - Syafrina, Nova; Hidayat, Arif (Eko dan Bisnis: Riau Economic and Business Review, 2021)
To attract consumers to make purchases, the company must be able to implement an appropriate marketing strategy in accordance with the market conditions faced. The success of a marketing strategy is influenced by several factors, namely market research and analysis, product decisions, pricing, sales promotion and distribution. This study examines how the influence of sales promotion on consumer decisions of Honda motorcycle credit service users at PT. Capela Multidana Pekanbaru Branch. Promotion is considered important because promotion is a form of communication and information between producers or product providers and the public or those who will consume the products they needFrom this research, the value of R2 or R Square is 0.310 or 31%. This value can be interpreted that changes in the value of Consumer Decisions are influenced by changes in the value of the Sales Promotion independent variable by 31% while 69% is determined by other variables that are not in this study.Â